Achieving Food and Nutrition Security: Lessons Learned from the Integrated Food Security Programme (IFSP), Mulanje, Malawi - Webb, Patrick (Tufts Archival Research Center, 2005)
Calls have been made recently for new approaches to the design and implementation of interventions aimed at achieving household food security; approaches that address more than just food availability by integrating actions enhancing food access and utilization as well. But what exactly should be integrated and how? This report represents a lessons learned assessment of an integrated agriculture, nutrition, and health intervention implemented in Malawi in the late 1990s and early 2000s. The review contributes to the ongoing international search for best practices in programming for food security. The Integrated Food Security Programme (IFSP) was designed as a self-reinforcing, synergistic program implemented in an area of extreme food insecurity. Nevertheless, the endline evaluation in 2004 reported that the intervention had achieved most of its aims. Child nutrition was improved (reaching the target set of a 10% reduction in the prevalence of stunting), and most sectoral targets in agriculture, income generating, and infrastructure development were also achieved. At roughly US$59 per household per year, the cost of the package of interventions integrated on the ground compares well with a range of other integrated programs in Malawi and elsewhere in the world. Importantly, many of the gains have been sustained.